Preparation of Ionic Conductivity Polymer Electrolyte Film Based on Epoxidized Deproteinized Natural Rubber - Trinh, Thi Hang; Le, Cao Chien; Bui, Thi Thanh Binh; Nguyen, Thi Hong Phuong; Kawahara, Seiichi; Phan, Trung Nghia (JST: Engineering And Technology For Sustainable Development, 2021)
Ionic conductivity polymer electrolyte film based on epoxidized deproteinized natural rubber (EDPNR) and lithium salt lithium triflate (LiCF₃SO₃) were prepared by solution casting technique. The EDPNR was prepared from deproteinized natural rubber latex (DNR) epoxidized in the latex stage with fresh peracetic acid 33%, which was deproteinized by incubation of the latex with 0.1 wt% urea and 1 wt% surfactant. The ionic conductivity of EDPNR mixed with lithium salt was investigated through impedance analysis. The results show that the conductivity of EDPNR/LiCF₃SO₃ mixture was dependent on LiCF₃SO₃ salt concentration and amount of epoxy group. The highest ionic conductivity at room temperature obtained is 1.71 × 10⁻⁵ S·cm⁻¹ at 35 wt% LiCF₃SO₃ and 45 mol% epoxy groups. Fourier transform infrared spectroscopy (FTIR) spectra showed evidence of complexation between EDPNR and LiCF₃SO₃. Glass transition temperature, Tg displayed an increasing trend with increasing salt concentration and epoxy group content.